Exploring your world the adventure of geography - National Geographic Society (U.S.). Special Publications Division (Washington, D.C. National Geographic Society, 1989)
A general encyclopedia of physical and human geography containing 334 alphabetically arranged entries and more than 1000 illustrations, including photographs, maps, and charts.
Includes bibliographical references.
Keywords: Geography -- Dictionaries